1983
DOI: 10.1002/lary.1983.93.10.1351
|View full text |Cite
|
Sign up to set email alerts
|

Primary Laryngeal Malignant Fibrous Histiocytoma: Review of the Literature and Report of Seven Cases

Abstract: After describing 4 new cases of malignant fibrous histiocytoma of the larynx (3 cases had been recently published), the authors review the literature, from which it appears that 16 such lesions of the larynx have been reported (including their 7 cases). Malignant fibrous histiocytoma usually occurs in the soft tissues, tendons and joints of the upper and lower extremities, and is uncommon in the head and neck--though not exceptional. The lesion is a mesenchymal tumor probably of histiocytic origin and may be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…(Ferlito, 1983). In MFH there are numerous typical and atypical mitotic figures, often with prominent areas of haemorrhage and necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…(Ferlito, 1983). In MFH there are numerous typical and atypical mitotic figures, often with prominent areas of haemorrhage and necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…The regimen consisted of cyclophosphamide in all cases, with additional doxorubicin, and methotrexate in the 1st case, with vincristine, procarbazine, and prednisone in the 2nd case, with doxorubicin, vincristine and prednisone in the 3rd, and with additional vincristine, and doxorubicin in the 4th case. They further suggested that inflammatory variant of malignant fibrous histiocytoma could be responsive to chemotherapy [25, 29, 30]. Phase II randomized trials conducted by The Sarcoma Alliance for Research Through Collaboration have shown that the combination of gemcitabine and docetaxel produced a 36% response rate (4 out 11 patients); this combination could be used for those patients refractory to cyclophosphamide/ifosfamide-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[2] It is uncommon in the head and neck region[2] and rare in the larynx. It has been reported that biopsy specimens of malignant fibrous histiocytoma in the head and neck region were initially diagnosed as fibrosarcomas or osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that biopsy specimens of malignant fibrous histiocytoma in the head and neck region were initially diagnosed as fibrosarcomas or osteosarcomas. [3–4] It is a mesenchymal tumor probably of histiocytic origin and may be divided into six subtypes,[2] i.e., pleomorphic, fibrous, giant cell, angiomatoid, myxoid and inflammatory, to be distinguished on the basis of the predominant feature. Surgery is the treatment of choice as radiotherapy and chemotherapy is not effective.…”
Section: Discussionmentioning
confidence: 99%